Putative Nucleotide-Based Second Messengers in the Archaeal Model Organisms Haloferax volcanii and Sulfolobus acidocaldarius - Braun, Frank; Recalde, Alejandra; Bähre, Heike; Seifert, Roland; Albers, Sonja-Verena (Frontiers in Microbiology, 2021)
Research on nucleotide-based second messengers began in 1956 with the discovery of cyclic adenosine monophosphate (3’,5’-cAMP) by Earl Wilbur Sutherland and his co-workers. Since then, a broad variety of different signaling molecules build form nucleotides has been discovered. These molecules fulfill crucial tasks in the context of intracellular signal transduction. The vast majority of the currently available knowledge about nucleotide-based second messengers originates from model organisms belonging either to the domain of eukaryotes or to the domain of bacteria, while the archaeal domain is significantly underrepresented in the field of nucleotide-based second messenger research. For several well-stablished eukaryotic and/or bacterial nucleotide-based second messengers, it is currently not clear whether these signaling molecules are present in archaea. In order to shed some light on this issue, this study analyzed cell extracts from two major archaeal model organisms, the euryarchaeon Haloferax volcanii and the crenarchaeon Sulfolobus acidocaldarius, using a modern mass spectrometry method for the presence of a broad variety of currently known nucleotide-based second messengers. The nucleotides 3’,5’-cAMP, cyclic guanosine monophosphate (3’,5’-cGMP), 5’-phosphoadenylyl-3’,5’-adenosine (5’-pApA), diadenosine tetraphosphate (Ap4A) as well as the 2’,3’-cyclic isomers of all four RNA building blocks (2’,3’-cNMPs) were present in both species. In addition, H. volcanii cell extracts also contain cyclic cytosine monophosphate (3’,5’-cCMP), cyclic uridine monophosphate (3’,5’-cUMP) and cyclic diadenosine monophosphate (3’,5’-c-di-AMP). The widely distributed bacterial second messengers cyclic diguanosine monophosphate (3’,5’-c-di-GMP) and guanosine (penta-)/tetraphosphate ((p)ppGpp) could not be detected. In summary, this study gives a comprehensive overview on the presence of a large set of currently established or putative nucleotide-based second messengers in an eury- and a crenarchaeal model organism.